2013
DOI: 10.1177/0003319712473796
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima Media Thickness and Its Association With Total Bilirubin Levels in Patients With Coronary Artery Ectasia

Abstract: Atherosclerosis plays an important role in the etiopathogenesis of coronary artery ectasia (CAE). The relationship between total bilirubin (TBil) and carotid intima media thickness (cIMT) in patients with CAE has not been fully investigated. Hence, we evaluated the relationship between TBil levels and cIMT in 142 consecutive eligible patients with CAE, newly diagnosed coronary artery disease (CAD), and normal coronary arteries. There were no significant differences in TBil (P = .772) and cIMT (P = .791) betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…We found that psoriasis patients without known cardiovascular risk factors had higher arterial stiffness when compared with healthy controls in a previous study (2). CIMT is now widely used as a surrogate marker for atherosclerotic disease (3). We also demonstrated that CIMT measurement was higher in patients with psoriasis compared to the control subjects (4).…”
supporting
confidence: 51%
“…We found that psoriasis patients without known cardiovascular risk factors had higher arterial stiffness when compared with healthy controls in a previous study (2). CIMT is now widely used as a surrogate marker for atherosclerotic disease (3). We also demonstrated that CIMT measurement was higher in patients with psoriasis compared to the control subjects (4).…”
supporting
confidence: 51%
“…2 cIMT is widely used as a surrogate marker for atherosclerotic disease based on inflammation. 4 In this context, we demonstrated that cIMT measurement is higher in patients with psoriasis compared with the control subjects. 5 So, it may be considered that increased inflammation of psoriasis contributes to atherogenesis and coronary artery disease.…”
mentioning
confidence: 74%
“…We investigated the relation between atherosclerosis and CIMT. We reported that CIMT was significantly higher in coronary artery disease(CAD) groups compared to control participants (3). We had also reported that CIMT levels were higher in newly diagnosed patients with untreated essential hypertension compared to controls(4).…”
Section: Accepted Manuscriptmentioning
confidence: 98%